Epigenetic therapy with inhibitors of histone methylation suppresses DNA damage signaling and increases glioma cell radiosensitivity - Gursoy-Yuzugullu, Ozge; Carman, Chelsea; Serafim, Rodolfo Bortolozo; Myronakis, Marios; Valente, Valeria [UNESP]; Price, Brendan D. (Impact Journals, 2017)
Radiation therapy is widely used to treat human malignancies, but many tumor types, including gliomas, exhibit significant radioresistance. Radiation therapy creates DNA double-strand breaks (DSBs), and DSB repair is linked to rapid changes in epigenetic modifications, including increased histone methylation. This increased histone methylation recruits DNA repair proteins which can then alter the local chromatin structure and promote repair. Consequently, combining inhibitors of specific histone methyltransferases with radiation therapy may increase tumor radiosensitivity, particularly in tumors with significant therapeutic resistance. Here, we demonstrate that inhibitors of the H4K20 methyltransferase SETD8 (UNC-0379) and the H3K9 methyltransferase G9a (BIX-01294) are effective radiosensitizers of human glioma cells. UNC-0379 blocked H4K20 methylation and reduced recruitment of the 53BP1 protein to DSBs, although this loss of 53BP1 caused only limited changes in radiosensitivity. In contrast, loss of H3K9 methylation through G9a inhibition with BIX-01294 increased radiosensitivity of a panel of glioma cells (SER2Gy range: 1.5 - 2.9). Further, loss of H3K9 methylation reduced DSB signaling dependent on H3K9, including reduced activation of the Tip60 acetyltransferase, loss of ATM signaling and reduced phosphorylation of the KAP-1 repressor. In addition, BIX-0194 inhibited DSB repair through both the homologous recombination and nonhomologous end-joining pathways. Inhibition of G9a and loss of H3K9 methylation is therefore an effective approach for increasing radiosensitivity of glioma cells. These results suggest that combining inhibitors of histone methyltransferases which are critical for DSB repair with radiation therapy may provide a new therapeutic route for sensitizing gliomas and other tumors to radiation therapy.
Keywords: DNA repair; G9a; Glioma; Histone methylation; Radiosensitizer